Evaluating the Quality of Randomized Trials Published in Persian Nursing Journals with More than 10 Years of Publishing Using the CASP Checklist - M Adib-Hajbaghery (نشریه پرستاری ایران, 2017)
Abstract Background & Aim: The quality of Randomized Controlled Trial (RCT) reports can significantly affect trust towards the results. However, the quality of RCTs published in Persian nursing journals has rarely been evaluated. This study aimed to evaluate the quality of RCTs published in Persian nursing journals. Materials & Methods: This is a descriptive cross-sectional study. The sample included 62 RCTs published from March 2015 to June 2016 in eight Persian nursing journals with at least 10 years of publishing history. A checklist, designed based on the CASP scale, was used to gather data. Descriptive statistics were used to analyze the data. Results: Out of 62 RCT papers, only three fully met the criteria. Only half of the papers used a formula to calculate the sample size. 48.39% of the papers did not report the type of randomization method and 74.20% did not explain how to allocate the participants to study groups. In 51.61% of the RCTs, the study groups were so different, which might have affected the results. In 53.33% of the articles, there was no report about blinding of the study. Although 98.39% of the papers reported the P value of the tests, only 4.84% of them reported the confidence interval. Conclusion: Most of the RCTs had deficiencies in reporting methodology and results. Deficiency in reporting the sample size calculation, randomization and allocation method, blinding method, and the confidence interval, were the most common problems in the RCTs.